INVENTARISASI HEWAN INVERTEBRATA PADA FILUM COELENTERATA DI PANTAI PONDOK PERMAI KABUPATEN SERDANG BEDAGAI, SUMATERA UTARA - RAHMADINA RAHMADINA; DWIKA ANANDA (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2018)
Coelenterates are called hollow animals because of their radial symmetry and only have a central cavity called the colenterata. Phylum Coelenterata is divided into 3 classes, namely Hydrozoa, Schyphozoa and Anthozoa. The literature study method used is based on the results of studies of various literature that have been tested for validity, are related to one another, are relevant to written studies and support the description or analysis of the discussion.